Detecting Ottokar II's 1248–1249 uprising and its instigators in co-witnessing networks. Issue 4 (2nd October 2022) - Ochab, Jeremi K.; Škvrňák, Jan; Škvrňák, Michael
Abstract: We provide a detailed case study showing how social network analysis allows scholars to detect an event affecting the entire historical network under consideration and identify the responsible actors. We study the middle 13th century in Czech lands, where a rigid political structure of noble families surrounding the monarchs led to the uprising of part of the nobility. Having collected data on approximately 2, 400 noblemen from 576 charters, we attempted to uncover social network features pointing to the rebellion and expose the noblemen who joined it. We observed, among other such quantifiable features, assortativity increasing before and resetting to random after the rebellion, a drop in the number of stable connections and subgraph similarity between yearly networks and regional titles (burgraves) rising in centrality above royal court officials in that period. The presented methods can be directly translated to other person-document data of comparable or larger sizes, and we hope it can help detect or disambiguate the timing of similar major events and the roles of people involved in them.